2015
DOI: 10.11648/j.ajcem.20150306.18
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Relative Bioavailability of Ambroxol Hydrochloride Aerosol and Injection

Abstract: Abstract:To compare the pharmacokinetics and relative bioavailability of ambroxol hydrochloride (AH) aerosol and injection, the volunteers were subjected to single-dose crossover inhalation (injection) of 100 mg AH aerosol (injection). The drug concentrations in plasma were determined by HPLC. The areas under curve (AUC) of the two formulations were compared by the three-factor analysis of variance and the bi-directional one-side t test. The C max , t max , t1/2β and AUC values of the aerosol group and the inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Phospholipid complexation exhibits two opposing effects on the bioaccessibility according to many studies. On the one side, when RA, or similar poorly absorbable compounds, are complexed with phospholipid, it has been observed that the aqueous solubility and dissolution rate were reduced in both acid media and alkaline phosphate buffer, although the amphiphilic structure of phospholipid was expected to enhance the dissolution [21,22,23]. Resulting from the low gel to liquid crystal transition temperature ( T m ), unsaturated phospholipids are difficult to formulate as fine powders under room temperature as the low Tm values and amorphous nature lead to sticky powders that are difficult to deaggregate [24,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Phospholipid complexation exhibits two opposing effects on the bioaccessibility according to many studies. On the one side, when RA, or similar poorly absorbable compounds, are complexed with phospholipid, it has been observed that the aqueous solubility and dissolution rate were reduced in both acid media and alkaline phosphate buffer, although the amphiphilic structure of phospholipid was expected to enhance the dissolution [21,22,23]. Resulting from the low gel to liquid crystal transition temperature ( T m ), unsaturated phospholipids are difficult to formulate as fine powders under room temperature as the low Tm values and amorphous nature lead to sticky powders that are difficult to deaggregate [24,25,26].…”
Section: Introductionmentioning
confidence: 99%